Cover Image, Volume 38, Issue 3. Issue 3 (March 2017) - Takeda, Kazuki; Kou, Ikuyo; Kawakami, Noriaki; Iida, Aritoshi; Nakajima, Masahiro; Ogura, Yoji; Imagawa, Eri; Miyake, Noriko; Matsumoto, Naomichi; Yasuhiko, Yukuto; Sudo, Hideki; Kotani, Toshiaki; et al.
Abstract : On the cover : The image, provided courtesy of Dr. G. Thomas Watters, Ohio State University, is based on the Original article, Compound heterozygosity for null mutations and a common hypomorphic risk haplotype in TBX6 causes congenital scoliosis, by Shiro Ikegawa et al., Pages 317–323. DOI:10.1002/humu.23168 .